Epileptiform Activity in Electroencephalogram of Normal Children - Darwish, Amira Hamed; Alshahawy, Azza Kamal; El-Shehaby, Walid Ahmed (Neuropediatrics, 2017)
Objectives This prospective cohort study assessed the prevalence of epileptiform discharges (EDs) in a cohort of healthy Egyptian children aged 1 to 18 years.Methods Children with a history of unprovoked seizure disorders, family history of epilepsy, neurological or psychological disorder, or any other chronic illness were excluded. Digital electroencephalogram (EEG) was recorded under resting condition for a minimum of 20 minutes including activation methods.Results The study included 1,382 healthy Egyptian children with no history of unprovoked seizures. Twenty-nine normal children had EDs, which represents 2.1% of total number of studied children. Centrotemporal spikes were detected in 19 children. The prevalence of EDs was significantly higher in children aged 6 to 12 years (3.59%) compared with children aged 13 to 18 years (1.2%) and children aged 1 to 5 years (0.45%).Conclusions EDs can be observed in nonepileptic normal children. Centrotemporal spikes are the most common epileptiform pattern in EEG of normal children. None of normal children with EDs developed seizures or other neurological disorders during follow-up.
Keywords: electroencephalogram; prevalence; normal children; epileptiform discharge